2016
DOI: 10.2169/internalmedicine.55.5209
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy to Effectively Treat a Patient with Behçet's Disease

Abstract: Behçet's disease (BD) is a polysymptomatic and recurrent systemic vasculitis with a chronic course and unknown cause. We herein report a 27-year-old woman who had suffered from a recurrent fever and tonsillitis for nearly ten years with BD for who tonsillectomy was effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The same 2 association peaks for ~30–31.5 Mb were associated with both these diseases. The authors of another study showed that tonsillectomy reduces signs and symptoms of Behcet’s disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same 2 association peaks for ~30–31.5 Mb were associated with both these diseases. The authors of another study showed that tonsillectomy reduces signs and symptoms of Behcet’s disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%